Does tenofovir gel or do other microbicide products affect detection of biomarkers of semen exposure in vitro?(, , ) - Snead, Margaret C. (Contraception, 2014)
OBJECTIVES: There is currently no information on whether products evaluated in HIV microbicide trials affect the detection of the semen biomarkers prostate-specific antigen (PSA) or Y chromosome DNA. STUDY DESIGN: We tested (in vitro) dilutions of tenofovir (TFV), UC781 and the hydroxyethylcellulose (HEC) placebo gels using the Abacus ABAcard and the quantitative (Abbott Architect total PSA) assays for PSA and Y chromosome DNA by real-time polymerase chain reaction. RESULTS: TFV gel and the HEC placebo adversely affected PSA detection using the ABAcard but not the Abbott Architect total PSA assay. UC781 adversely affected both the ABAcard and Abbott Architect total PSA assays. While there were some quantitative changes in the magnitude of the signal, none of the products affected positivity of the Y chromosome assay. CONCLUSIONS: The presence of TFV or HEC gels did not affect quantitative PSA or Y chromosome detection in vitro. Confirmation of these findings is recommended using specimens obtained following use of these gels in vivo. IMPLICATIONS: Researchers should consider the potential for specific microbicides or any products to affect the particular assay used for semen biomarker detection. The ABAcard assay for PSA detection should not be used with TFV UC781, or HEC.